PATHOGENESIS, CLINICS AND METHODS OF THERAPY OF GESTATION DIABETES - Тішков, Олександр (SWorldJournal, 2022)
The work is devoted to the treatment of diabetes mellitus in pregnant women, as one of the most common endocrine pathologies, which has a negative tendency to increase. The article examines the mechanisms of occurrence and development of gestational diab